2017
DOI: 10.3892/ol.2017.6157
|View full text |Cite
|
Sign up to set email alerts
|

Flexible magnifying endoscopy with narrow band imaging for the diagnosis of uterine cervical tumors: A cooperative study among gastrointestinal endoscopists and gynecologists to explore a novel microvascular classification system

Abstract: Abstract. Narrow band imaging with magnifying endoscopy (NBI-ME), which is useful for the assessment of micro-vessels, has excellent diagnostic potential for early gastrointestinal epithelial neoplasia. Conventional diagnostic tools for uterine cervical epithelial tumors are still unsatisfactory. An accurate diagnostic tool for uterine cervical epithelial tumors is required to preserve the reproductive ability of young women with uterine cervical tumors. Flexible NBI-ME was performed in patients with cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Endocytoscopy might be useful for determination of the need for conization. Recently, there have been a few reports on the usefulness of flexible magnifying endoscopy with narrow band imaging (ME-NBI) for evaluation of CIN [15,16]. ME-NBI visualizes microstructures of the mucosa showing microvascular features with 80-100-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Endocytoscopy might be useful for determination of the need for conization. Recently, there have been a few reports on the usefulness of flexible magnifying endoscopy with narrow band imaging (ME-NBI) for evaluation of CIN [15,16]. ME-NBI visualizes microstructures of the mucosa showing microvascular features with 80-100-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been a few reports on the usefulness of exible magnifying endoscopy with narrow band imaging (ME-NBI) for evaluation of CIN [15,16]. ME-NBI visualizes microstructures of the mucosa showing microvascular features with 80-100-fold.…”
Section: Discussionmentioning
confidence: 99%
“…In areas suspicious for ≥CIN2, magnifying observation was performed as necessary ( Figure 3 b). The diagnostic criteria for the ≥CIN2 lesions were based on our previous studies as follows: the presence of thick white epithelium or thin white epithelium plus atypical vessels or dense acetowhite epithelium (W2) [ 5 , 6 ]. White epithelium was defined as thin white epithelium when the underlying vessels were visible, and thick white epithelium when the underlying vessels were invisible.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in combination with magnifying endoscopy (ME), it visualizes microvascular architecture and microsurface structure that correspond with histology. We have developed a novel method that uses flexible gastrointestinal ME-NBI for the diagnosis of CIN [ 5 ]. We found that the ME-NBI showed the characteristic findings of CIN better than colposcopy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%